Differences in the effect of second-generation antipsychotics on prolactinaemia: six weeks open-label trial in female in-patients - Svestka, Jaromír; Synek, Oldrich; Tomanová, Jana; Rodáková, Irena; Cejpková, Andrea (Neuro endocrinology letters, 2007)
OBJECTIVES: The main objective was to evaluate the effect of five second-generation antipsychotics (amisulpride, quetiapine, olanzapine, risperidone, and zotepine) on prolactinaemia during 6 week therapy in 433 female in-patients with mainly schizophrenic disorders. Secondary objectives included identification of dynamics of change in serum prolactin levels and correlations of changes of prolactinaemia with some demographic and clinical parameters. METHODS: The trial was a prospective, open-label, single-center one with a flexible dosing of SGAs. The therapeutic effect of SGAs was assessed by a change of scores of CGI-S and CGI-I scales from a baseline to the endpoint. Blood samples were taken in the morning under fasting condition. RESULTS: Amisulpride and risperidone increased prolactinaemia significantly in 100% of patients, as early as after week 1 of the therapy. Quetiapine and zotepine relatively reduced prolactinaemia significantly, as early as from week 1 of the quetiapine treatment. Olanzapine led to a transient mild prolactin elevation. The much lower prevalence of hyperprolactinaemia over 2 000 mIU/l differentiates olanzapine from amisulpride and risperidone. Prolactin elevation did not correlate with age, menopausal condition, therapeutic efficacy, antipsychotic daily dose, serum levels of lipids and glucose. There was significant correlation with first vs. subsequent psychotic episodes, weight, EPS and serum levels of thyroid hormones. CONCLUSION: Amisulpride and risperidone had marked and early prolactin elevating effects, requiring, therefore, more frequent monitoring of prolactinaemia and associated undesirable effects and risks than olanzapine, quetiapine and zotepine.
Keywords: Benzodiazepines; Amisulpride; amisulprid; Risperidone; Olanzapine; Middle Aged; risperidon; neparametrická statistika; Adolescent; Statistics, Nonparametric; Schizophrenia; quetiapin fumarát; Dibenzothiepins; Adult; Aged; dospělí; dibenzothiepiny; Prospective Studies; senioři; prolaktin; mladiství; benzodiazepiny; dibenzothiazepiny; senioři nad 80 let; Quetiapine Fumarate; lidé; Prolactin; ženské pohlaví; Humans; Sulpiride; schizofrenie; Aged, 80 and over; Hyperprolactinemia; Antipsychotic Agents; sulpirid; Female; Dibenzothiazepines; lidé středního věku; antipsychotika; olanzapin; hyperprolaktinemie; prospektivní studie